Проблема соотношения конусности и размера эндодонтического инструмента (Эндодонтия Today, 2020)
Machinary rotary instruments develop continuously, their design changes, in order to remove the root dentin more effectively and form optimal taper of a canal. The more pronounced taper increases the probability of tooth fracture. At machine treatment of root canal the taper of instruments should be increased gradually. Machine rotary instruments are constantly improving, changing their design, which ensures effective removal of root dentin, forming an optimum taper of the canal. Creating too pronounced taper increases the probability of fracture of the tooth. When treating the root canal taper instruments should be increased gradually, ensuring the smooth expansion of the root canal. This allows to prevent many complications associated with endodontic treatment of teeth.